Effects of the enlargement of EU on trade and the environment - Xueqin Zhu; Ekko van Ierland (Fondazione Eni Enrico Mattei (FEEM), 2001)
With the gradual accession of some Central Eastern European Countries (CEECs) to the EU, international trade between EU and CEECs and the related environmental problems will definitely change because of the free trade and the mobility of production factors (labour and capital) within the EU. This paper investigates the consequences of the enlargement of the EU on trade and environment by general equilibrium modelling. A general equilibrium model with the sequential joint maximisation method is developed to examine the impacts under different environmental regimes. For illustrative purposes, the model is applied in a numerical example with two regions (EU and CEECs) and two goods (pollution intensive good A and clean good B). The model is also run for some important environmental policies. The result show that the 'coordinated policy in EU and CEECs' could be efficient to restrict the total emission level for uniformly mixing pollutants.
Keywords: C68; D58; F18; 330; Trade and environment; environmental policy; AGE models; sequential joint maximisation; Negishi-format; EU-Erweiterung; Internationale Wirtschaft; Umweltbelastung; Umweltpolitik; EU-Staaten; Osteuropa